B-Learning utilizando software libre, una alternativa viable en Educación Superior - González Mariño, Julio César (Revista Complutense de Educación, 2006)
There is no doubt that it is necessary to include in the education new practices and models more appropriate in the information society. This work analyzes the viability to incorporate the Blended Learning model in education through a virtual environment of learning based on free software (Moodle) and the implantation of a continuous formation program to the teaching staff, in order to give a goodquality education. Blended Learning combines the best thing of the actual instruction with functionalities of e-learning, to take advantage of the strengths and to diminish the weaknesses of both modalities.